Microstructure and Slip Character in Titanium Alloys - Banerjee, D.; Williams, J. C. (Defence Science Journal, 2014)
Influence of microstructures in titanium alloys on the basic parameters of deformation behaviour such as slip character, slip length and slip intensity have been explored. Commercial titanium alloys contain the hexagonal close packed (alpha) and body centred cubic (bita) phases. Slip in these individual phases is shown to be dependent on the nature of alloying elements through their effect on phase stability as related to decomposition into ordered or w structures. When alpha and bita coexist, their relative crystallographic orientations, size, shape and volume fraction, control the nature of slip. For a given composition, structure may be manipulated through appropriate thermomechanical treatment to obtain the desired deformation behaviour and therefore fracture mode.